Exploring the Selling Skills of Tiangge Market Vendors in Guagua, Pampanga: A Phenomenological Study - Butiu, Joy Vee A.; Candelaria, Roxanne F.; Cayde, Guada Marie B.; Clitar, Mary Elizabeth R.; Dayao, Ronel M.; Tayag, James Mathew R.; Chingcuangco, Jhon Ian L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
In the Philippine market, the tiangge sector continues to manifest strong growth despite setting lower prices for their products. This qualitative phenomenological research examined the selling skills of 12 tiangge vendors in Guagua, Pampanga, exploring their lived experiences and business strategies. Employing a semi-structured, open-ended interview guide and thematic analysis, the study gathered in-depth insights into the vendors' experiences and selling practices. The findings indicated that these vendors mostly exhibited skills in bargaining, relationship-building, communication, integrity, problem-solving, referrals, adaptability, and positive thinking. However, these selling skills were often challenged by factors such as low income, rental expenses, weather conditions, the threat of e-commerce, unpleasant customers, and work-related burnout. The vendors’ resilience in hurdling these challenges was attributed to coping strategies including spiritual and family motivations, opportunity recognition, the suki (loyal customer) system with price flexibility, and product diversification aligned with market trends.